On the upturn phenomenon in the strength vs. strain-rate relations of metals. (30th November 2019) - Rosenberg, Z.; Kositski, R.; Ashuach, Y.; Leus, V.; Malka-Markovitz, A.
Abstract: The dynamic response of metals and their alloys to high strain-rate loading is examined in this work. Particularly, we focus on the controversy surrounding a claim, made by several authors, that the flow stresses of various materials experience a very large increase (the "upturn" phenomenon) at strain rates in the range of 10 3 –10 4  s −1 . This claim was contradicted by other workers who did not find such an "upturn" behavior for the same materials, at this range of strain rates. We review some of these works and identify possible reasons for this discrepancy, focusing on the differences between the experimental techniques which were used in the various studies.